Ethical Implications of Digital Technologies on Socioeconomically Disadvantaged Communities in Nigeria - Ogwuegbu, David Azunna; Ajobiewe, Damilola Nnamaka (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2025)
Digital technologies have the potential to revolutionize a nation’s socioeconomic system. The Nigerian experience buttresses the influence of these innovative tools. Although the penetration and prevalence of digital transformation are a welcome development, it raises ethical concerns, especially as regards the underprivileged within the nation. This paper explores the ethical considerations of digital technologies on these vulnerable groups. Issues discussed include low smartphone penetration, high cost of data, limited digital literacy, and infrastructural challenges. Recommendations were given, which include regular monitoring and evaluation of current practices, and designing of digital transformation initiatives with inclusive policies that address systemic inequalities, and collaborative efforts between the government, private sector, and non-governmental organisations.